Application of spatiotemporal scan statistics in cases of intentional homicides in northern Brazil - Alves, Henrique José de Paula; Batista, Ben Dêivide de Oliveira (Brazilian Journal of Biometrics, 2024)
The crime of intentional homicide in Brazil is worrying. In the northern region, this type of crime has been growing since 2020. In this sense, we decided to apply Kuldorff's prospective space-time scan statistics in order to identify emerging counties. We conclude that there are two emerging clusters of high relative risk (Amazonas and Pará) that require rapid intervention and two clusters of low relative risk (Acre, Roraima, Amazonas, Amapá and Pará) that do not require urgent intervention. Some characteristics of these two clusters are presented: radius, population, relative risk, likelihood ratio.